M-banking: Salah Satu Layanan Jasa Bank Yang Menjadi Faktor Penting Dalam Mendapatkan Kepuasan Nasabah - Henry Fransisko Paniroi; Erika Hardiyanti Kusuma Dewi; Muhammad Irsad K (Pajak dan Manajemen Keuangan, 2024)
In the rapidly evolving digital era, mobile banking services have emerged as one of the forefront innovations in the banking industry. This article discusses the importance of customer satisfaction through mobile banking services as a crucial banking service. Adopting a qualitative approach, this research utilizes data from 10 questionnaire responses to analyze the four dimensions of mobile banking quality: convenience, security, ease of use, and design. Additionally, the study considers aspects of communication and customer service. The results of the analysis indicate that customer satisfaction plays a significant role in building a strong relationship between banks and customers. By optimizing the quality of mobile banking services, including convenience, security, ease of use, and design, banks can ensure better customer satisfaction, enhance customer loyalty, and strengthen their position in an increasingly competitive market. The interpretation of the data also provides personal recommendations as an additional aspect, emphasizing the importance of improving critical aspects of mobile banking services. These recommendations reinforce the conclusion that focusing on customer satisfaction will help banks achieve a competitive advantage in the current digital era.